Patient engagement partnerships in clinical trials (PEP-CT): protocol for the systematic development and testing of patient partner and investigator decision aids. Issue 2 (21st February 2022) - Parry, Monica; Ceroni, Tina; Wells, David; Richards, Dawn P; Toupin-April, Karine; Ansari, Hafsa; Bjørnnes, Ann Kristin; Burnside, Heather; Cavallo, Sabrina; Day, Andrew; Ellis, Anne; Feldman, Debbie; et al.
Abstract : Introduction: Building capacity to improve sex/gender knowledge and strengthen patient engagement in clinical trials requires training and support. The overall goal of this 2-year project is to refine, translate and evaluate two web-based open-access patient and investigator decision aids aimed to improve patient engagement partnerships in clinical trials. Methods and analysis: Two decision aids were designed in Phase 1 of this programme of research and this protocol describes a subsequent sequential phased approach to refine/translate (Phase 2A) and conduct alpha/usability (Phase 2B) and beta/field (Phase 3) testing. Decision aid development is guided by the International Patient Decision Aid Standards, User-Centred Design, Ottawa Decision-Support Framework and the Ottawa Model of Research Use. We have integrated patient-oriented research methods by engaging patient partners across all phases of our programme of research. Decision aids will first be refined and then translated to French (Phase 2A). Eight iterative cycles of semistructured interviews with 40 participants (20 patient partners and 20 investigators) will be conducted to determine usability (Phase 2B). A pragmatic pre/post pilot study design will then be implemented for field/beta testing using another purposive sample of 80 English-speaking and French-speaking participants (40 patients and 40 investigators). The samples are purposive to ensure an equal representation of English-speaking and French-speaking participants and an equal representation of men and women. Since sex and/or gender differences in utilisation and effectiveness of decision aids have not been previously reported, Phase 3 outcomes will be reported for the total sample and separately for men and women. Ethics and dissemination: Ethics approval has been granted from the University of Toronto (41109, 28 September 2021). Informed consent will be obtained from participants. Dissemination will include co-authored publications, conference presentations, educational national public forums, fact sheets/newsletters, social media sharing and videos/webinars.